A Pilot Mindfulness Intervention to Reduce Heavy Episodic Drinking. Issue 2 (30th June 2021) - Cotter, Elizabeth W.; Hawthorne, David J.; Gerker, Colin; Norman, Marianne; Fotang, Jenny P.
Abstract : Approximately one third of college students report heavy episodic drinking (HED; Substance Abuse and Mental Health Services Administration, 2019), defined as four or more drinks for women and five or more drinks for men on a single occasion. This mixed‐methods study examined the feasibility of a mindfulness intervention intended to reduce HED. Thirty‐six students were assigned to either (a) a 4‐week mindfulness intervention or (b) a personalized email. The mindfulness group reported fewer weekend night drinks postintervention. Adaptations that can reduce barriers to attendance will be needed.